Peran Religiusitas Orang Tua Terhadap Nilai Agama dan Moral Pada Anak Usia 3 Tahun - Delvi. A. S Pakaya; Yusnita Umar; Sasti Abdullah; Nurur. F. H Abodale; Sri Rawanti (Student Journal of Early Childhood Education, 2023)
Religious education is education that prepares students to be able to carry out roles that require mastery of knowledge about religious teachings or become religious experts who practice their religious teachings. For this reason, this research aims as an effort to face challenges in the era of the all-digital era, every human being needs an optimization to explore the capabilities of an individual himself. Here, by giving a foundation for moral and religious education to children, this potential will increase if it becomes a habit or adjustment from an early age because in this case children can distinguish between good and bad behavior, right and wrong and carry out their religious teachings habitually. according to their level of growth and development. In instilling religious and moral values in children does not have to be hard and forceful, therefore teachers and parents are required to increase insight, understanding, skills for moral and religious development in early childhood.